Network optimizations in the Internet of Things: A review - N.N. Srinidhi; S.M. Dilip Kumar; K.R. Venugopal (Engineering Science and Technology, an International Journal, 2019)
The Internet was initially used to transfer data packets between users and data sources with a specific IP address. Due to advancements, the Internet is being used to share data among different small, resource constrained devices connected in billions to constitute the Internet of Things (IoT). A large amount of data from these devices imposes overhead on the IoT network. Hence, it is required to provide solutions for various network related problems in IoT including routing, energy conservation, congestion, heterogeneity, scalability, reliability, quality of service (QoS) and security to optimally make use of the available network. In this paper, a comprehensive survey on the network optimization in IoT is presented. The paper draws an attention towards the background of IoT and its distinction with other technologies, discussion on network optimization in IoT and algorithms classification. Finally, state-of-the-art-techniques for IoT in particular to network optimization are discussed based on the recent works and the review is concluded with open issues and challenges for network optimization in IoT. This paper not only reviews, compares and consolidates the recent related works, but also admires the author’s findings, solutions and discusses its usefulness towards network optimization in IoT. The uniqueness of this paper lies in the review of network optimization issues and challenges in IoT. Keywords: Congestion, Energy conservation, Network optimization, QoS, Reliability